Thermal Degradation Kinetics of Polyvinyl Chloride Stabilized with Palm Based Mixed Metal Carboxylates - Putrawan, I Dewa Gede Arsa; Hasibuan, Michael Jaya Sebastian; Nainggolan, Stevanus Newman; Aprilia, Elsa Dwi (ASEAN Journal of Chemical Engineering, 2025)
Despite its diverse applications, especially as building materials, polyvinyl chloride (PVC) is easily degraded by heat. Thermal degradation poses a significant problem during extrusion, with the worst case being that the PVC resins cannot be formed into final products. Additionally, the degradation process releases hydrogen chloride, which is harmful to the environment. Mixed metal (Ca/Zn) carboxylates are popular PVC thermal stabilizers, offering a more environmentally friendly alternative to lead salts and a more cost-effective option than organotin, another commonly used industrial thermal stabilizer. However, conventional mixed Ca/Zn thermal stabilizers, typically based on stearic acid, remains relatively costly for PVC compounders in developing countries. Recently, we have developed a Ca/Zn thermal stabilizer from palm fatty acid distillate (PFAD), referred to as Ca/Zn Palmate. This thermal stabilizer is as effective as the conventional stearic-acid-based Ca/Zn thermal stabilizer but significantly more affordable, owing to the lower cost of PFAD. Continuing this research, we studied the thermal degradation kinetics of PVC resin stabilized with the developed palm-based mixed Ca/Zn thermal stabilizer. Degradation data were collected from dehydrochlorination tests carried out within the 170-190°C temperature range, with varying doses of Ca/Zn Palmate, Ca/Zn ratios, and co-stabilizer amounts. The degradation followed the A2 model of Avrami-Erofeev. The activation energy for unstabilized PVC was found to be 124.4 kJ/mol, while for stabilized PVC, it ranged from 128.8 to 167.2 kJ/mol. The results showed that increasing the Ca/Zn Palmate dose or the Ca/Zn ratio led to higher activation energy. The highest activation energy occurred when the co-stabilizer doses were equivalent to the dose of Zn Palmate.